Analisis Pengaruh Rekrutmen dan Pelatihan terhadap Kinerja Karyawan: Studi Kasus pada PT PLN UP3 Banda Aceh - Masyithah, Syarifah Mauli; Muhammad; Zuliani; Ivana , Farah; Mediyanti , Sisca; Jumeil, T Muhammad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of recruitment and training on employee performance at PT PLN UP3 Banda Aceh. The research problem centers on the importance of effective recruitment and training processes in enhancing employee productivity and performance. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to 55 employees of PT PLN UP3 Banda Aceh. The data were analyzed using multiple linear regression, including both partial (t-test) and simultaneous (F-test) analyses. The results indicate that both recruitment and training variables have a significant partial effect on employee performance. Furthermore, the simultaneous test confirms that these two variables jointly have a significant impact on performance. These findings highlight the critical role of improving recruitment quality and training programs in boosting human resource performance within the company.